2021
DOI: 10.1161/jaha.120.018549
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 and Development of Heart Failure With Preserved Ejection Fraction in the General Population

Abstract: Background The cause of heart failure with preserved ejection fraction (HFpEF) is poorly understood, and specific therapies are lacking. Previous studies suggested that inflammation plays a role in the development of HFpEF. Herein, we aimed to investigate in community‐dwelling individuals whether a higher plasma interleukin 6 (IL‐6) level is associated with an increased risk of developing new‐onset heart failure (HF) over time, and specifically HFpEF. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 48 publications
(57 reference statements)
4
42
1
Order By: Relevance
“…The “upstream” proinflammatory biomarkers IL-1 and IL-6 act as important initiators of inflammation and can trigger a cascade of inflammatory mediators, such as CRP and fibrinogen ( 44 ). Although evidence from preclinical and clinical studies suggested that the IL-1-IL-6 signaling pathway led to impaired systolic and diastolic cardiac function ( 45 ), clinical trials choosing these pathways as anti-inflammatory therapeutic targets have reported controversial results. Administration of anakinra, an IL-1 receptor antagonist, yielded beneficial effects on aerobic capacity improvement but did not reduce the length of hospital stay or rehospitalization in HF ( 14 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The “upstream” proinflammatory biomarkers IL-1 and IL-6 act as important initiators of inflammation and can trigger a cascade of inflammatory mediators, such as CRP and fibrinogen ( 44 ). Although evidence from preclinical and clinical studies suggested that the IL-1-IL-6 signaling pathway led to impaired systolic and diastolic cardiac function ( 45 ), clinical trials choosing these pathways as anti-inflammatory therapeutic targets have reported controversial results. Administration of anakinra, an IL-1 receptor antagonist, yielded beneficial effects on aerobic capacity improvement but did not reduce the length of hospital stay or rehospitalization in HF ( 14 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel evidence emerged strengthening the inflammatory paradigm and reinforcing research for anti-cytokine biological therapy in HFpEF (Paulus and Zile, 2021). For example, higher IL-6 levels were demonstrated to be associated with an increased risk of developing HFpEF (Chia et al, 2021) and circulating levels of TNF-α receptor 2 were shown to be increased in association with the degree of diastolic dysfunction in patients with HFpEF but not HFrEF (Putko et al, 2014). Also, (anti-inflammatory) high density lipoprotein cholesterol/(inflammatory) CRP ratio was shown to be a useful marker for prognostication and correlated with echocardiographic parameters in HFpEF patients (Yano et al, 2021).…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…High hsCRP, TNF-α, and TGF-β levels increase the susceptibility to cardiac damage in hypertensive patients with the metabolic syndrome, in whom they are independently related to the LV mass index and diastolic LV dysfunction ( 65 ). In accordance, elevated TNF-α and IL-6 independently predict incident HFpEF, the predominant type of HF in obesity and diabetes, but not HF with reduced ejection fraction (HFrEF) ( 266 , 267 ). Subjects with obesity or diabetes account for the majority of the HFpEF patient population in which pathophysiological pathway analyses demonstrated a close link to vascular cell adhesion, leucocyte migration and inflammation ( 268 ).…”
Section: Clinical Perspectivementioning
confidence: 68%